Fifteen simulated patient working formats to use in communication skills training: Report of a survey. (2nd December 2021) - Bank, Ivan; Rasenberg, Ellemieke M. C.; Makkenze-Mangold, Sara H.; Nelissen, Sandy; van Wijngaarden, Jacqueline; Lovink, Annelies G.; Rethans, Jan-Joost
Abstract: Objective: Simulated and standardized patients (SPs) are increasingly being used in communication skills training for healthcare professionals' education. Despite this broad use of SPs, there is no recent literature with an overview on SP working formats being used. We ran a study to fill this gap. Methods: First, a survey on formats on the use of SPs in various curricula for education of healthcare professionals in Belgium and The Netherlands was run by members of the Dutch Association of Medical Education Special Interest Group on Simulated and Standardized patients (SIG-NL/B). Then the SIG-NL/B organized a national workshop where professionals working with or interested in SPs were invited to come forward with SP working formats they used. They were also asked to provide relevant details about the use. Finally, the outcomes of these two phases were combined. Results: Fifteen SP working formats were found. Six of them were described before. The details of all formats are listed and discussed. Conclusion: We categorised 15 SP working formats. The choice to use a particular format is mainly based on the learning objectives of the session involved and the expertise at hand.